Food practices and climate change: the potential of pedagogical vegetable gardens - Aguiar , Denise Regina da Costa; Cirilo , Delma Maria Correia; Resende, Flavia Grecco; Dall’Agnol , Marcia (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
This study aimed to investigate the potentialities of implementing pedagogical vegetable gardens for the development of Food Projects and actions to reduce the greenhouse gas emissions. The research was developed through a qualitative approach, with documentary analysis and the review of scientific papers. The implementation of the pedagogical vegetable garden, in formal and non-formal scopes, can be a way for socio-environmental changes and for the construction of more conscious knowledge and attitudes of the population towards the preservation of the environment. It was concluded that pedagogical vegetable garden projects are powerful in food education and in mitigating the disposal of solid waste to the environment and, consequently, in reducing the emission of greenhouse gases.
Keywords: Social and Environmental Rights; . School Feeding; Critical Environmental Education